A relação entre inteligência emocional e mindfulness em estudantes universitários - Costa, Islana Ferreira (Universidade Federal de São Carlos, 2020)
Emotional Intelligence (EI) and Mindfulness have been widely studied in recent years. EI involves cognitive skills of emotions, while Mindfulness works awareness of the present moment and what is being lived. Mindfulness has been related to the improvement of information within the individual, such as emotion, so studies have been done to prove this association. Thus, the goal of this research was to contribute with more data about the relationship between EI and Mindfulness, taking as a sample the Brazilian population. 129 individuals of both sexes participated in the study (Women N = 101, 78.3%; Men N = 28, 21.7%) aged between 18 and 68 years (M = 26.82; SD = 11,746, Md = 21), students from two different universities from the state of Sao Paulo, Brazil. Participants answered three assessment instruments: the FFMQ-BR - Five Facet Mindfulness Questionnaire; ICE 3.0 - Emotional Skills Inventory; and BIE - Emotional Intelligence Assessment Battery, as well as a sociodemographic questionnaire. The results showed that gender did not affect the level of EI or Mindfulness, but the age group did, and older participants had higher scores for both phenomena. The relationship between the two constructs is significant, positive and moderate considering the self-report EI, but only a few significant correlations were observed for performance EI. Furthermore, a Regression Analysis was made and it showed that the facets Observation, Description and Non-Reactivity, of Mindfulness, were predictors of self-report EI. The facet Act with Awareness, of Mindfulness, and Age were predictors of performance EI.
The relationship between emotional intelligence and mindfulness in university students
La relación entre inteligencia emocional y mindfulness en estudiantes universitarios
Keywords: Emoção; Inteligência emocional; Emotion; Emotional intelligence; Mindfulness; CIENCIAS HUMANAS::PSICOLOGIA